Fabrication of collagen immobilized electrospun poly (vinyl alcohol) scaffolds. (17th April 2015) - Oktay, Burcu; Kayaman‐Apohan, Nilhan; Erdem‐Kuruca, Serap; Süleymanoğlu, Mediha
<x xml:space="preserve">Abstract</x> In the development of tissue engineering scaffolds, the interactions between material surface and cells play crucial roles. The biomimetic 3‐D scaffolds absolutely provide better results for fulfilling requirements such as porosity, interconnectivity, cell attachment and proliferation. In this study, 3‐D electrospun scaffolds were prepared by using an electrospinning technique. Photo cross‐linkable polyvinyl alcohol was used as a polymeric matrix. During the electrospinning, the nanofibers were cross‐linked with in situ ultraviolet radiation. The crosslinked polymer fibers were achieved in a simple process at a single step. Nanofiber surface was modified with collagen by a chemical approach. The chemical structures were proven by attentuated total reflectance Fourier transform infrared spectroscopy and proton nuclear magnetic resonance. The surface morphology of the nanofibers was characterized by scanning electron microscope (SEM). Morphological investigations show that the resulting nanofibrous matrix has uniform morphology with a diameter of 220–250 nm. In vitro attachment and growth of 3T3 mouse fibroblasts and human umbilical vein endothelial cells (ECV304) cells on polyvinyl alcohol‐based nanofiber mats were also investigated. Cell attachment, proliferation, and methylthiazole tetrazolium cytotoxicity assays indicated good cell viability throughout the culture time, which was also confirmed by SEM analysis. Copyright © 2015 John Wiley & Sons, Ltd.